Case Report: Recurrent Hemiplegic Migraine Attacks Accompanied by Intractable Hypomagnesemia Due to a de novo TRPM7 Gene Variant - Lei, Meifang; Wang, Ping; Li, Hong; Liu, Xiaojun; Shu, Jianbo; Zhang, Qianqian; Cai, Chunquan; Li, Dong; Zhang, Yuqin (Frontiers in Pediatrics, 2022)
Transient receptor potential melastatin 7 (TRPM7) is a ubiquitously expressed chanzyme comprised of a divalent cation channel permeable to calcium and magnesium and a cytosolicserine-threonine α-kinase domain. TRPM7 has a crucial role in magnesium ion homeostasis and anoxic neuronal death, which was identified as a potential non-glutamate target for hypoxic ischemic neuronal injury. TRPM7 is implicated in ischemic stroke and hypomagnesemia in many studies, but it has not been clearly associated with disease in OMIM database. No clinical cases between TRPM7 gene variants and hypomagnesemia have been reported so far. One patient with recurrent hemiplegic migraine attacks accompanied by intractable hypomagnesemia was followed up in Tianjin Children's Hospital from 2018 to 2021. We systematically summarized and analysed the clinical manifestations, imaging features, and serum magnesium changes of the patient. Genetic analysis was performed by whole exome sequencing and Sanger sequencing to infer the etiology of hemiplegic migraine attacks and hypomagnesemia in this patient. Gene sequencing revealed a novel heterozygous variant of TRPM7 gene (c.2998A>G, p.Met1000Val) which has not been reported previously, this is also a de novo variant that is not inherited from his parents. We described a novel variant p.Met1000Val (c.2998A>G) located in the transmembrane region of TRPM7 protein, which is possibly crucial for the normal function of ion channel. Our study expands the variation spectrum of TRPM7 gene, highlights the importance of molecular genetic evaluation in patients with TRPM7 gene deficiency, and demonstrates the causal relationship between TRPM7 gene variants and disease manifestations.